Knowledge, Attitude and Practices regarding Cardiovascular Diseases among people of Pakhribas municipalty of Eastern Nepal - Shrestha, Manisha; Pyakurel, Prajjwal; Yadav, Kamlesh Prasad; Singh, Sweta; Priyadarshini, Soumya; Rajak, Bolbam; Sinha, Aditya; Aprajita, Aprajita; Kumari, Ira; Jha, Narendra Mohan; Prassan, Netra; Tripathi, Saloni; et al. (Nepalese Heart Journal, 2020)
Background and Aims: Cardiovascular diseases (CVDs) are the leading cause of death globally with 17.9 million deaths in 2016. Nepal is facing a high burden of non-communicable diseases (NCDs) with 66% of people dying from NCDs in 2018. In this study, we aim to assess the knowledge, attitudeand practice regarding CVDs among people of Pakhribas Municipality in Eastern Nepal. Methods: Observational cross-sectional study was conducted among residents of Pakhribas Municipality in eastern Nepal from 9th December to 22nd December 2018. We recruited a convenient sample of 458 permanent residents of Pakhribas municipality. A semi-structured questionnaire based on the CARRF-KL scale survey for knowledge, attitude and practice (after thorough literature review) was used to elicit the information. Descriptive and thematic analysis was done. Result: Fifty-five percent of the respondents belonged to the age group of 30-60 years. Half of the respondents were females. Janjati community was the most dominant ethnicity. One-fourth of the participants were illiterate. The knowledge was found to be average with only 51.5% realizing that family history of CVDs increases the risk of CVDs. Similarly, 46% didn’t know that coronary heart disease could be prevented. The attitude was found to be good with 90.4%, 93.6% and 90.6% respectively stating that they will exercise more, change eating habits and quit smoking if they had CVDs. Regarding practices, people visit traditional healers when they are ill and drink alcohol to fight cold despite knowing it as a risk factor for CVDs. Conclusion: The knowledge of people of Pakhribas Municipality regarding CVD was average. However, the attitude was good. Regarding the practice, people have mixed practices.